Severe hyponatraemia during sepsis and marijuana addiction. (29th March 2011) - Catalano, Concetta; Seck, Sidy; Enia, Giuseppe
Abstract : The authors report a 29-year-old kidney transplant patient who presented, four episodes of severe hyponatraemia associated with sepsis from 2006 to 2010. He was a long-term user of marijuana. The association between severe recurrent hyponatraemia during sepsis and marijuana addiction might not be casual, since experimental data show that vasopressin release induced by sepsis is modulated by the endocannabinoid system.